Collagenopathies—Implications for Abdominal Wall Reconstruction: A Systematic Review. Issue 10 (October 2016) - Harrison, Bridget; Sanniec, Kyle; Janis, Jeffrey E.
Abstract : Background: The etiology of hernia formation is strongly debated and includes mechanical strain, prior surgical intervention, abnormal embryologic development, and increased intraabdominal pressure. Although the most common inciting cause in ventral hernias is previous abdominal surgery, many other factors contribute. We explore this etiology through an examination of the current literature and existing evidence on patients with collagen vascular diseases, such as Ehlers–Danlos syndrome. Methods: A systematic review of the published literature was performed of all available Spanish and English language PubMed and Cochrane articles containing the key words "collagenopathies, " "collagenopathy, " "Ehlers-Danlos, " "ventral hernia, " and "hernia." Results: Three hundred fifty-two articles were identified in the preliminary search. After review, 61 articles were included in the final review. Conclusions: Multiple authors suggest a qualitative or quantitative defect in collagen formation as a common factor in hernia formation. High-level clinical data clearly linking collagenopathies and hernia formation are lacking. However, a trend in pathologic studies suggests a link between abnormal collagen production and/or processing that is likely associated with hernia development.